Monitoring the antimicrobial activity of bentonite-chlorhexidine hybrid. (March 2023) - de Oliveira, Luís H.; de Lima, Idglan S.; dos Santos, Adriana N.; Trigueiro, Pollyana; Barreto, Humberto M.; Cecília, Juan Antonio; Osajima, Josy A.; da Silva-Filho, Edson C.; Fonseca, Maria G.
Abstract: Clay mineral-based antimicrobial materials have been widely investigated as effective alternatives for preventing and controlling infectious diseases. In this study, we evaluated the incorporation of different concentrations of chlorhexidine into sodium bentonite by monitoring the interaction between the clay sample and organic molecules. The antibacterial activity of the hybrids against Staphylococcus aureus and Escherichia coli was also evaluated using the direct contact test. The obtained hybrids were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), zeta potential measurements, CHN elemental analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and thermogravimetric analysis (TG/DTG). Chlorhexidine was successfully intercalated into clay, as confirmed by increased basal spacing from 1.26 nm to 1.56 nm. The maximum amount of chlorhexidine incorporated was 689 mg g −1, and the characterizations indicated that electrostatic attraction and hydrogen bonding were involved in the formation of chlorhexidine/bentonite hybrids. Antibacterial testing of the hybrids revealed up to 100% inhibition of both the bacteria. These results are promising because the superior antibacterial activity of chlorhexidine/bentonite hybrids indicates that these materials can be used to control the spread of pathogens in the environment, thereby contributing to the prevention of infectious diseases. Graphical Abstract: ga1 Highlights: Chlorhexidine/bentonite hybrids with antibacterial action were prepared. The hybrids were obtained in different chlorhexidine concentrations. Interactions between the species were evaluated. Antibacterial activities against S. aureus and E. coli were evaluated. High antibacterial activity against both bacteria was observed.